Association of clinical and radiological factors with the outcomes of central venoplasty among end-stage renal dis-ease patients in Hospital Universiti Sains Malaysia. - Puteh, Othman (2023)
Background: Central venous stenosis is a common complication in end-stage renal disease patients receiving hemodialysis therapy, and central venoplasty is currently the mainstay treat-ment. However, not all patients undergoing central venoplasty have a successful outcome. This study aims to determine the association between radiological factors and clinical factors deter-mining the success rate of central venoplasty. Methodology: A retrospective cross-sectional study was conducted in Advanced Minimally Invasive Endovascular and Neurointervention (AMIEN) Unit, Hospital Universiti Sains Ma-laysia (HUSM) on 62 patients with central venous stenosis or occlusion and were treated with central venoplasty in Hospital HUSM 1st January 2016 until 31st August 2020. Radiological variables (location, grade, and length of stenosis) and clinical variables (gender, diabetes melli-tus (DM), and hypertension (HPT) were assessed before central venoplasty. The association between the radiological and clinical factors with the outcome of central venoplasty was cal-culated using Chi-Square Test. Results: A total of 62 patients were included in our study. There was no significant association between the location of veins, degree, and length of stenosis with the successful outcome. However, a single vein had a significantly higher success rate (92.6%) than multiple veins (7.4%). Apart from the radiological factors, the clinical factors (gender, DM, and HPT) also show no significant association in determining successful outcomes with p values 0.159, 0.644 and 0.283 respectively (more than 0.05). Conclusion: There is no association between clinical and radiological factors with the out-comes of central venoplasty among end-stage renal disease patients. A further study needs to be conducted with a larger sample size and other possible determining factors to help facilitate the procedure in the future.